The Problem Elite’s Identity of Lithuania Minor: Cultural Discourse - Strakauskaitė, Nijolė (Sociologija. Mintis ir veiksmas, 2001)
The aim of the article is to discuss the identity of the elites in Lithuania Minor. The analysis of the elite’s identity is developed in the context of Prussian system of education. The author argues that the schools played an important role in the development of the self-consiousness of the group and suggests that the tension between traditional and pragmatist outlooks is defining of their idendity.